Advertisement Remove all ads

Balance the Equation Stepwise. Naoh(Aq) + H2so4(Aq) → Na2so4(Aq) + H2o(L) - Science and Technology 1

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Short Note

Balance the equation stepwise.

NaOH(aq) + H2SO4(aq) → Na2SO4(aq) + H2O(l)

Advertisement Remove all ads

Solution

NaOH(aq) + H2SO4(aq) → Na2SO4(aq) + H2O(l)
Step1. Count the number of each atom in reactant side:
Na= 1
H=3 
O=5
S=1
Step2. Count the number of each atom in product side:
Na= 2
H=2
O=5
S=1
Step3.Then balance the number of each atom in an equation by multiplying reactant and product side with numeral value:
If we multiply NaOH by 2 in the reactant side and H2O by 2 in the product side, then number of atoms in product and reactant side gets balance.
2NaOH(aq) + H2SO4(aq) → Na2SO4(aq) +2H2O(l)

Concept: Chemical Equation
  Is there an error in this question or solution?

APPEARS IN

Balbharati Science and Technology Part 1 10th Standard SSC Maharashtra State Board
Chapter 3 Chemical reactions and equations
Q 7.4 | Page 46
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×